PENGARUH KEPATUHAN SUSTAINABILITY REPORTING BERDASARKAN GRI STANDARDS TERHADAP OPINI AUDIT GOING CONCERN DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur di BEI Tahun 2022–2024) - Bunga Viva Salsabella; Herry Laksito (Diponegoro Journal of Accounting, 2026)
A Going concern audit opinion is issued by an auditor when there is doubt about a company’s ability to continue its operations in the future. This study aims to examine the effect of compliance with sustainability reporting based on the GRI Standards on Going concern audit opinions and to analyze the role of Firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The variables used in this study are sustainability reporting compliance as the independent variable, Firm size as the moderating variable, and Going concern audit opinion as the dependent variable.The object of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The sample was selected using a purposive sampling technique with certain criteria. The analytical method used in this study is logistic regression using SPSS software.The results show that sustainability reporting compliance does not have a significant effect on Going concern audit opinions. In addition, Firm size is not able to moderate the relationship between sustainability reporting compliance and Going concern audit opinions.